Norway : Selected Issues. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2017)
This paper examines various factors driving the uptrend in house prices, with a particular focus on institutional and structural factors. The extent of a possible valuation gap is gauged empirically in the context of a cross-country panel analysis of long-run fundamental determinants of house prices using data from 20 OECD countries. Norway has seen a long housing boom since the mid-1990s apart from a brief and mild downturn during the global financial crisis, with house price inflation exceeding income growth by a wide margin. Although real house prices have also been up strongly during the same period in the majority of advanced economies, Norway experienced one of the highest increases in the OECD. With house prices rising ahead of income, the average cost of a home relative to the median household income nationwide has almost doubled since the mid-1990s, rising much faster than OECD average. In absolute terms, the house price-to-income (PTI) ratio is also high relative to a range of countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet